THE ROLE OF SOCIAL MEDIA IN SHAPING DEMOCRATIC ELECTIONS: AN ANALYTICAL STUDY - Kumar, Rakesh; Singh, Sugan (International Journal of Research -GRANTHAALAYAH, 2025)
The proliferation of social media has transformed modern political communication, reshaping how information is produced, disseminated and consumed during electoral processes. This analytical study examines the expansive role of social media in elections, addressing its influence on voter engagement, political mobilization, campaign strategies, public discourse and the eventual (democratic) outcomes. Drawing on theoretical frameworks from political communication, media studies and behavioral science, this paper critically evaluates both the emancipatory potentials and the democratic challenges introduced by digital platforms in electoral contexts, with some brief allusions towards the Indian context as well.